EMERGENCE OF METABOLIC SYNDROME IN POLICE PROFESSIONALS: A LONGITUDINAL OBSERVATIONAL STUDY - Pattojoshi, Amrit; Shit, Bhabani Shankar; Sinha, Satish Kumar; Idrees S A; Sinha, Niska (Student’s Journal of Health Research Africa, 2023)
Objective: This is a longitudinal observation looking for the emergence of metabolic syndrome (MetS) in a rapid response police unit. Methods: After taking informed consent, measurements were taken of blood pressure, body mass index (BMI), waist circumference, triglycerides, HDL-cholesterol, and fasting blood glucose periodically in 2019, 2021, and 2023 in January. 146 police officers enrolled out of 148 screened and 117 completed the study. Results: In four years, the proportion of individuals with MetS values exceeding the norm increased by 20-30% for each component with 56 new cases of impaired metabolic parameters and 13 new cases of MetS observed among 110 previously unaffected police officers. Conclusion: A significant increase in the number of Metabolic Syndrome was found, particularly via its effects on blood lipid levels in police personnel which a highly stressful for professionals. Future longitudinal studies with continuous stress monitoring and comparing with a control will more in-depth knowledge into it.